Bridging the Gap: CGIAR Initiative on Market Intelligence and Global Market Intelligence Platform (GloMIP) for Informed Decision-Making in Crop Breeding - Paguirigan, Neale Marvin; Lenaerts, Bert; De Leon, Dehner; Ynion, Jhoanne; Bayot, Ruvicyn; Demont, Matty (International Rice Research Institute, 2023)
Over the past decades, CGIAR breeding programs have faced slow varietal turnover in farmers’ fields, partially due to limited information on drivers of varietal replacement. Genetic Innovation decisions within CGIAR-NARES predominantly follow a supply-driven approach, misaligning the needs of farmers, agribusinesses, and consumers. Hence, the CGIAR must revisit and design target product profiles (TPPs) for future crop varieties guided by insights from market intelligence. Therefore, the CGIAR Initiative on Market Intelligence was established to provide timely and reliable data, insights, and information to effectively guide decision-making and maximize return on investments in breeding pipelines and seed systems. This initiative entails five intervention areas, referred to as Work Packages. All market intelligence information will be centralized in a novel platform known as the Global Market Intelligence Platform (GloMIP).